CONSIDERATION OF JUDGES OF THE PANDAN RELIGIOUS COURT IN DETERMINING THE STATUS OF THE DEFENDANT / INVISIBLE APPLICANT: MAQASHID AL-USRAH PERSPECTIVE - Imam Yazid; Nurcahaya Nurcahaya; Fikri Al Muhaddits (UNISSULA, 2023)
This article aims to find out what the judge considers in determining the status of the defendant/respondent in absentia. Then, the consideration is analyzed using the maqashid al-usrah theory which is part of the maqashid al-syariah study. The judge's consideration referred to here is the consideration of the judge of the Pandan Religious Court, which is limited to occult divorce cases, to be precise Decision Number 33/Pdt.G/2020/PA.Pdn and Decision Number 24/Pdt.G/2020/PA.Pdn. This decision is interesting to discuss, because the entire determination of the invisibility limit in the Pandan Religious Court does not have a definite time limit, including these two decisions. The methodological flow of this research uses a normative legal research format, with primary legal materials (secondary data), Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, and copies of Decision Number 33/Pdt.G/2020/PA.Pdn and Decision Number 24/Pdt.G/2020/PA.Pdn. The results of the study show that in the two decisions, it must be distinguished between the judge's consideration in determining the status of the defendant/respondent in occultation and the judge's consideration in breaking the marriage bond between the litigants. Regarding the determination of the status of the respondent/applicant as invisible, it turned out that the judge was not guided by Islamic law (fiqh mazhab), but rather the general civil procedural law. As for the reason for dissolving the marriage, the judge saw that the marriage of the litigants no longer fulfilled the elements to achieve the purpose of marriage; if the family is maintained, it will bring mafsadah. It can be concluded that the judge's consideration in each decision is in accordance with maqashid al-usrah.